Time-Resolved Study of Site-Specific Corrosion in a Single Crystalline Silver Nanoparticle - Steffen Trautmann; André Dathe; Andrea Csáki; Matthias Thiele; Robert Müller; Wolfgang Fritzsche; Ondrej Stranik (Nanoscale Research Letters, 2019)
Abstract We followed over 24 h a corrosion process in monocrystalline triangular-shaped nanoparticles at a single-particle level by atomic force microscopy and optical spectroscopy techniques under ambient laboratory conditions. The triangular-shaped form of the particles was selected, because the crystallographic orientation of the particles is well defined upon their deposition on a substrate. We observed that the particles already start to alter within this time frame. Surprisingly, the corrosion starts predominantly from the tips of the particles and it creates within few hours large protrusions, which strongly suppress the plasmon character of the particles. These observations support the crystallographic model of these particles consisting of a high-defect hexagonal closed packed layer, and they could help material scientists to design more stable silver nanoparticles. Moreover, this described technique can be used to reveal kinetics of the corrosion in the nanoscale of other materials.